Observations on the Electrical Activity in the Olfactory Epithelium and Tract of Some Fishes - van Dijk, Clasina (My University, 1963)
In this investigation the electrophysiological response to stimulation of the olfactory epithelium in response to trout scent and some of its chemical components was studied. Recordings were made both from the lamprey nasal sac and the catfish olfactory tract and the various responses described and compared with responses measured by other authors.
Electrical Activity in the Olfactory System of Some Fishes
Keywords: electric; olfactory; olfactory epithelium; fish